Acquiring research‐grade ERPs on a shoestring budget: A comparison of a modified Emotiv and commercial SynAmps EEG system. (12th May 2017) - Barham, Michael P.; Clark, Gillian M.; Hayden, Melissa J.; Enticott, Peter G.; Conduit, Russell; Lum, Jarrad A. G.
Abstract: This study compared the performance of a low‐cost wireless EEG system to a research‐grade EEG system on an auditory oddball task designed to elicit N200 and P300 ERP components. Participants were 15 healthy adults (6 female) aged between 19 and 40 ( M = 28.56; SD = 6.38). An auditory oddball task was presented comprising 1, 200 presentations of a standard tone interspersed by 300 trials comprising a deviant tone. EEG was simultaneously recorded from a modified Emotiv EPOC and a NeuroScan SynAmps RT EEG system. The modifications made to the Emotiv system included attaching research grade electrodes to the Bluetooth transmitter. Additional modifications enabled the Emotiv system to connect to a portable impedance meter. The cost of these modifications and portable impedance meter approached the purchase value of the Emotiv system. Preliminary analyses revealed significantly more trials were rejected from data acquired by the modified Emotiv compared to the SynAmps system. However, the ERP waveforms captured by the Emotiv system were found to be highly similar to the corresponding waveform from the SynAmps system. The latency and peak amplitude of N200 and P300 components were also found to be similar between systems. Overall, the results indicate that, in the context of an oddball task, the ERP acquired by a low‐cost wireless EEG system can be of comparable quality to research‐grade EEG acquisition equipment.